Socio-cultural Life of Dura: A Sociological Case Study From Khaje Gaun, Lamjung - Adhikari, Bishow Bandhu (Dhaulagiri Journal of Sociology and Anthropology, 2006)
DOI: 10.3126/dsaj.v1i0.292 Dhaulagiri Vol.1 (2005) pp.220-237